Mitigating Climate Change... Reaping bumper harvest of tubers in adverse conditions - Ravi, V.; Chakrabarti, S. K.; Saravnan, R. (Indian Horticulture, 2019)
Introduction: Tropical root and tuber crops are highly remunerative since they are climate resilient. A large population in Tamil Nadu and Andhra Pradesh depend upon cassava for their livelihood. Often tropical root and tuber crops, particularly cassava, could substitute paddy, sugarcane and maize which require more water. Sweet potato could sustain food supply in Odisha in super-cyclone during 1999. A vast population in hilly regions in Kerala, Odisha and Andhra Pradesh depend upon cassava and sweet potato as a staple food. The root and tuber crops sustain food supply during the time of famine. Thus these crops definitely have high relevance to combat abiotic stresses in the context of climate change.